The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1002/eji.1830190319
|View full text |Cite
|
Sign up to set email alerts
|

Specific immune responses restored by alteration in carbohydrate chains of surface molecules on antigen‐presenting cells

Abstract: Two class I major histocompatibility (MHC) mutant mouse strains, H-2bm14 and H-2bm6, differ from the strain of origin C57BL/6 (B6, H-2b) in one and two amino acids of the H-2Db and H-2Kb molecule, respectively. The bm14 Db mutation results in specific failure of female bm14 mice to generate a cytotoxic T lymphocyte (Tc) response to the male-specific antigen H-Y. The allospecific Tc response of CD8+ B6T cells against bm6 Kb mutant spleen cells, in contrast to that against other Kb mutants, is absolutely CD4+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 46 publications
0
47
0
Order By: Relevance
“…Our ability to detect cell surface molecules wilh MoAb suggests that it is unlikely that a protective halo was masking antigenic molecules and preventing contact with alloreactive PBMC, Qualitative differences in the MHC class I and II molecules of different cell types also occur. Il has recently been shown that dendritic ceils, which are potent APC, possess fewer sialic acid molecules on ihcir surface and that removal of sialic acids by neuraminidase can restore responses to otherwise non-stimulalory APC [61]. Furihermore, as was shown by others for tibroblasts.…”
Section: Discussionmentioning
confidence: 75%
“…Our ability to detect cell surface molecules wilh MoAb suggests that it is unlikely that a protective halo was masking antigenic molecules and preventing contact with alloreactive PBMC, Qualitative differences in the MHC class I and II molecules of different cell types also occur. Il has recently been shown that dendritic ceils, which are potent APC, possess fewer sialic acid molecules on ihcir surface and that removal of sialic acids by neuraminidase can restore responses to otherwise non-stimulalory APC [61]. Furihermore, as was shown by others for tibroblasts.…”
Section: Discussionmentioning
confidence: 75%
“…Since, on the other hand, DC-derived restriction elements were found to be more efficient in stimulating allogeneicTcells than B cell-derived molecules it was proposed that the charge of the sialic acid residues impairs the interaction between the Tcell antigen receptors and the MHC molecules [37]. Although a comparable degree of sialylation of the polymorphic chains and of the invariant chains y and p40 was detectable (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…As a nonmutually exclusive explanation, structural features of MHC class II may exist that are specific for DCs but are not found on other APCs (43). Such a condition may result in an altered MHC class II affinity for TCRs and for CD4 molecules resulting in improved Lck activation.…”
Section: Discussionmentioning
confidence: 99%